Utilization of Various Vegetable Insecticides to Control Grayak Caterpillars (Spodoptera litura) on Soybean (Glycine max L. Merrill) in Laboratory - Azwana Azwana; Saipul Sihotang (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this study was to observe the effect of various vegetable insecticide extracts on controlling armyworm (Spodoptera litura) on soybean plants in the laboratory. The research was conducted at the Plant Protection Laboratory, Faculty of Agriculture, University of Medan Area, from November 2021 to April 2022, using a Completely Randomized Design (CRD) Non Factorial, consisting of 7 treatment levels, namely: N0 = no treatment (control), N1 = Mindi leaf extract concentration 5% (50 m/l water), N2 = Mindi leaf extract 10% (100 ml.l water), N3 = Mindi leaf extract concentration 15% (150 m/l water), N4 Babadotan concentration 5 % (50 ml/l air), N5 = 10% concentration of Babadotan leaf extract (100 ml/lair), N6 = 15% concentration of Babadotan leaf extract (150 ml/lair), with repetition 3. Parameters observed for Armyworm Mortality (%), LC50, LT50, the proportion of the effectiveness of vegetable insecticides on armyworm mortality and the amount of feed consumed. The results showed that the application of vegetable insecticides had a significant and very significant effect on armyworm mortality from 4 days after application to 10 days after application with the highest mortality proportion at a concentration of 15%. The LC50 values of the plant insecticides mindi leaves and babadotan leaves were almost the same, namely 4.69 and 4.48%. The LT 50 value for a concentration of 15% showed that babadotan leaf extract was faster than mindi leaf extract, namely mindi leaves 5.145 days and babadotan leaves 4.633 days. Concentrations of 10 and 15 % of the 2 plant extracts tested showed the same effectiveness on mortality of S. litura caterpillars and higher dissolving concentrations of 5%. The amount of feed consumed was also significantly different with the highest amount of feed in the control treatment (60.75 g) followed by the treatment of mindi leaves and babadotan leaves at concentrations of 15, 10, and 5%.